CREATION OF ELECTRONIC INFORMATION LEARNING ENVIRONMENT OF UNIVERSAL EDUCATION SCHOOLS AND DEVELOPMENT OF INFORMATION COMMUNICATION COMPETENCE (ICC) IN STUDENTS - Haytbayeva Sayyora Rakhimberganovna (Journals Park Publishing, 2024)
This article describes the pedagogical foundations of creating an electronic information learning environment of general education schools and developing students' information and communication competence. focused. The meaning of the concept of "information communication competence" in the educational system has been revealed.
Keywords: electronic information educational environment, information and communication competence, educational and methodological support, modern information technologies, informatization of education, computer literacy.